Investigation on Dynamic Recrystallization Behavior of Martensitic Stainless Steel - Facai Ren; Fei Chen; Jun Chen (Advances in Materials Science and Engineering)
The hot deformation behavior of X20Cr13 martensitic stainless steel was studied using the hot compression flow curves corresponding to the temperature range of 900–1150°C under strain rates from 0.01 to 10 s−1. A new mathematical model to estimate the flow stress under hot deformation conditions up to the peak of the flow curves was developed. The critical strains for initiation of dynamic recrystallization were also derived by the developed model. Furthermore, the effects of Zener-Hollomon parameter on the characteristic points of the flow curves were studied using the power law relation. The deformation activation energy obtained for this steel was 359.4 kJ/mol in the temperature range from 900°C to 1150°C. At the same time, the Avrami kinetic equation of dynamic recrystallization for X20Cr13 steel and the recrystallized grain size model were also established. Good agreement was obtained between the predictions and the experimental values.